FRI0068 SAFETY OF THE ZOSTER RECOMBINANT ADJUVANTED VACCINE IN RHEUMATOID ARTHRITIS PATIENTS: A SINGLE CENTER'S EXPERIENCE WITH 300 PATIENTS. (June 2019) - Stevens, Emma; Weinblatt, Michael E.; Massarotti, Elena; Griffin, Frances; Desai, Sonali
Abstract : Background: Patients with rheumatoid arthritis (RA) and other systemic rheumatic diseases (SRD) are at increased risk of developing Herpes Zoster (HZ) due to the diseases/or medications used to treat them such as corticosteroids methotrexate, biologic disease modifying agents, and JAK inhibitors. Released in 2018, the Zoster Recombinant Adjuvanted (ZRA) is a new vaccine with >90% efficacy and can be used in patients taking immunosuppressive therapy as compared to the live Zoster vaccine 1 . There has been a concern about whether the potency of the adjuvant could trigger flares of the underlying SRD, and whether there will be more side effects in this population. Objectives: Our goal was to study the impact of the new ZRA vaccine in RA and other SRD patients and to measure the risk of flare and incidence of side effects. Methods: We performed a retrospective chart review from 2/1/2018 to 1/20/2019, on patients with RA and SRD seen at the BWH who had received the ZRA vaccine. Co-variates of interest were collected. A flare was defined as occurring within 12 weeks of the vaccine administration by either: 1) documentation of RA flare in the rheumatologist office notes, telephone encounter or patient portal communication, or 2) new prednisone prescription or an increase in dose of existing prednisone prescription. Vaccine side effects were defined as muscle soreness at the injection site, redness, mild swelling, fatigue, fevers, myalgias, headaches, nausea, and abdominal pain. Results: 300 patients who received the new ZRA vaccine between 2/1/2018 to 1/20/2019 were identified. Mean follow up was 12.5 weeks ranging from 1-40 weeks following administration. Patient characteristics are identified in Table 1 . We identified a 3.00% (n=9) incidence of flare following the first dose and 2.86% (n=4) incidence following the second dose. One patient flared after both the first and second dose. All the flares were mild, self-limited, responded to treatment with low dose glucocorticoids, and did not warrant a change in immunosuppressive therapy. 15.3% (n=46) patients experienced side effects such as soreness at the injection site, fever, stomach ache, and flu like symptoms. Of the patients who experienced side effects, 15.4% (n=40) occurred after the first dose and 8.59% (n=11) occurred following the second dose. Five patients experienced side effects from both. All side effects were regarded as mild and did not necessitate an emergency room visit. No cases of Zoster were reported. Conclusion: In our experience with 300 patients who received the new ZRA (207 RA and 93 SRD) in 2018-2019, the incidence of disease flares was ≤ 3% and of side effects was 15% which is reassuring. Both flares and side effects were mild, self-limited, and did not require a change in DMARD therapy. No cases of Zoster were reported. Larger formal studies with longer term follow up are required to confirm our findings. Reference: [1] Shingrix Recommendations.cdc.gov. https://www.cdc.gov/vaccines/vpd/shingles/hcp/shingrix/recommendations.html Disclosure of Interests: Emma Stevens: None declared, Michael E. Weinblatt Shareholder of: Stock option: CanFite, Lycera, Scipher, Inmedix, Grant/research support from: Crescendo Bioscience, Bristol Myers Squibb, Sanofi, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, CanFite, Corrona, Crescendo, GlaxoSmithKline, Gilead, Horizon, Lilly, Lycera, Merck, Novartis, Pfizer, Roche, Samsung, Scipher, Set Point, Elena Massarotti : None declared, Frances Griffin: None declared, Sonali Desai : None declared